2019
DOI: 10.1158/1541-7786.mcr-18-0341
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells Promote Colorectal Cancer Cell Survival by Activating the HER3-AKT Pathway in a Paracrine Fashion

Abstract: The regulation of colorectal cancer cell survival pathways remains to be elucidated. Previously, it was demonstrated that endothelial cells (EC) from the liver (liver parenchymal ECs or LPEC), the most common site of colorectal cancer metastases, secrete soluble factors in the conditioned medium (CM) that, in turn, increase the cancer stem cell phenotype in colorectal cancer cells. However, the paracrine effects of LPECs on other colorectal cancer cellular functions have not been investigated. Here, results sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 44 publications
1
48
0
Order By: Relevance
“…Studies have shown that PRL3 is associated with increased metastatic potential in several cancers including CRC 9,32,33 . PRL3 has been reported to activate PI3K/Akt signaling in different cancer cell models 18,34 and we have shown that PRL3 activates Akt through phosphorylation at serine 473 in colon cancer cells 4 . In the present study, we investigated the levels of PRL3 and phosphorylated Akt (S473) expressions in 26 paired human CRC primary tumor and liver metastatic tissue specimens using IHC methods.…”
Section: Resultsmentioning
confidence: 90%
“…Studies have shown that PRL3 is associated with increased metastatic potential in several cancers including CRC 9,32,33 . PRL3 has been reported to activate PI3K/Akt signaling in different cancer cell models 18,34 and we have shown that PRL3 activates Akt through phosphorylation at serine 473 in colon cancer cells 4 . In the present study, we investigated the levels of PRL3 and phosphorylated Akt (S473) expressions in 26 paired human CRC primary tumor and liver metastatic tissue specimens using IHC methods.…”
Section: Resultsmentioning
confidence: 90%
“…Endothelial and vascular blood vessel cells have a function beyond supplying nutrition to tumor tissues; they also act as cancer niche cells and create a cancer‐promoting environment 68 . For example, endothelial cells can stimulate and activate colorectal cancer stem cells in a paracrine or juxtacrine fashion by mediating Notch and Akt signaling 69,70 . Similarly, lymphatic endothelial cells can activate metastatic signatures 71,72 and immunoregulatory function 73 in gastric cancers via secretion of soluble factors, suggesting a paracrine tumor‐promoting function of endothelial cell lineage in gastric cancers.…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…Swarnali Acharyya et al first described that endothelial cells were involved in the development of chemoresistance of breast cancer via secretion of TNF-a (12). Increasing evidence has demonstrated that endothelial cells contribute to chemoresistance of cancer cells by secreting soluble factors in a paracrine fashion in lymphoma (13)(14)(15), glioblastoma (16,17), colorectal cancer (18,19), and other cancer types (20)(21)(22)(23). Results from these studies showed that secreted factors including exosomes from endothelial cells can activate "cancer-advancing" signaling pathways in cancer cells such as AKT, Wnt, NOTCH, and epithelial-mesenchymal transition pathways in favor of survival under chemotherapy.…”
Section: Introductionmentioning
confidence: 99%